Pengaruh Kepuasan Kerja, Motivasi Dan Lingkungan Kerja Fisik Terhadap Produktivitas Karyawan Cv Inti Mitra Wahana Medan - Sinto Sinto; Sri Puspa Dewi; Dita Adriani Putri (Universitas Islam Sumatera Utara, 2022)
This research was conducted at the secretariat at CV Inti Mitra Wahana Medan, which aim of to determine the effect of jab satisfaction, motivation and physical work environment play a role in increasing employee productivity. This study used quantitative methods, where the population in this study was 40 employees, and the sample taken was as much as 100% of the total population because the number was not up to 100 people. The results of this research show that partially physical work environment (X3) have a significant effect on employee productivity within the CV Inti Mitra Wahana Medan (Y), with a t calculate value of 2,770 and a significance level value of 0.003 smaller than 0.05. Meanwhile, simultaneously, both job satisfaction (X1), motivation (X2) and employee productivity (X3) have a significant effect on the employee productivity within the sCV Inti Mitra Wahana Medan , with a F calculated value of 3,161 and a significant level value of 0.036 less than 0.05.